Design of 30 A PWM Type Solar Charge Controller Module for 100 Watt Lamp Load - Imaduddin, Ilmir Rizki; Basri, Muhammad Hasan; Mujib, Abdul; Rahman, Moh. Taufiqur; Khairudin, Ahmad Vardin; Eka, Sefri Aditya; Husen, Moh.; Fatoni, Isbet (Journal of Electrical Engineering and Computer (JEECOM), 2024)
The electrical energy produced by solar panels has been used as a renewable energy solution to support human life. In reality, this alternative energy has not been widely used due to the constraints of expensive initial investment, so it is necessary to design solar power generation components, one of which is a reliable, optimal, efficient and economical solar charge controller. The controller is made using the switching method. The switching process can occur by setting the duty cycle through the embedded controller in the solar charge controller circuit. Based on the test results, a duty cycle value of 1% to 100% can occur the switching process. The duty cycle that has been set on the solar charge controller is 90%. The duty cycle is a duty cycle where the output voltage approaches the setpoint of the minimum charger voltage. The input voltage from the solar panel when connected to the battery of ±16 volts can be regulated to ±14 volts by the solar charge controller. Based on the battery charging specifications, the controller output can be used to charge a 12 volt battery.